Application of Artistic Research Models to Improve the Variety of Research and the Quality of Student's Thesis in the Department of Fine Arts FBS Unimed - Daulat Saragi; Osbert Sinaga; Nelson Tarigan (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2021)
This research is motivated by the problem of the model and theme of student thesis research in the fine arts study program so far there has been no novelty. This is evidenced by the thesis that only repeats the theme and object of previous research. The purpose of the research is to apply a research model oriented to textbook products that have an impact on improving the quality and variety of students' thesis research objects. Knowing the effectiveness of the use of teaching materials developed and applied. It is hoped that with this textbook, student thesis research will be varied and touch more on the field of quality art. The research model used with 4D Thiagarajan is define, design, develop, and desiminate. Subjects are students of semester VI totaling 2 classes (32 people) and the object in this study is an art research model. The data collection instrument used was in the form of a questionnaire of students' interest and interest in the applied textbooks. In this study, the quality of research results is measured by the usefulness of the product that has been validated. The results showed that the student's response to the research product reached good and positive criteria. The effectiveness of textbooks developed with various research models is very good. It is recommended that this art research model textbook can be applied by lecturers and students of Fine Arts at FBS Unimed and other universities. In this study, the quality of research results is measured by the usefulness of the product that has been validated. The results showed that the student's response to the research product reached good and positive criteria. The effectiveness of textbooks developed with various research models is very good. It is recommended that this art research model textbook can be applied by lecturers and students of Fine Arts at FBS Unimed and other universities. In this study, the quality of research results is measured by the usefulness of the product that has been validated. The results showed that the student's response to the research product reached good and positive criteria. The effectiveness of textbooks developed with various research models is very good. It is recommended that this art research model textbook can be applied by lecturers and students of Fine Arts at FBS Unimed and other universities.